Randomised controlled trial of nicotine chewing-gum. Issue 6341 (21st August 1982) - Jarvis, M J; Raw, M; Russell, M A; Feyerabend, C
Abstract : The effectiveness of 2 mg nicotine chewing-gum as an aid to stopping smoking was compared with a placebo containing 1 mg nicotine, but unbuffered, in a double-blind randomised trial. Of 58 subjects given the active gum, 27 (47%) were not smoking at one-year follow-up compared with 12 (21%) of the 58 subjects treated with placebo (p less than 0.025). By the most stringent criterion of outcome, 18 (31%) subjects in the active treatment group and eight (14%) in the placebo group had not smoked at all from the start of treatment to follow-up at one year (p less than 0.05). Subjects receiving the active gum experienced less severe withdrawal symptoms and rated their gum as more helpful than did the placebo group. Minor side effects were common but only gastric symptoms were more frequent with the active gum. Subjects receiving active gum used it for longer than those receiving placebo but most stopped using it within six months and only four (7%) developed longer-term dependence. The number of gums used daily correlated significantly with pretreatment blood nicotine concentrations in the active treatment group and with pretreatment cigarette consumption in the placebo group. A lower pretreatment blood nicotine value was the best predictor of success at one year (p less than 0.001) but there was no significant relation to cigarette consumption, sex, and social class. The results clearly confirm the usefulness of nicotine chewing-gum as an aid to stopping smoking and imply a definite role for nicotine in cigarette dependence and withdrawal. Successful use of the gum requires careful attention to subjects' expectations and clear instructions on how to use it.